2022
DOI: 10.1002/lno.12187
|View full text |Cite
|
Sign up to set email alerts
|

Functional responses of aggregate‐colonizing copepods

Abstract: Zooplankton consumption of aggregates, such as marine snow, is an important factor in determining the efficiency of the biological carbon pump. However, the feeding rates of aggregate-associated small harpacticoid and poecilostomatoid copepods are largely unknown, as are the factors that influence these rates. We measured the functional responses of pellet production (PP) of aggregate-feeding copepods on appendicularian houses, algal and detrital aggregates, and on Trichodesmium spp. tufts. The PP rates of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
5
1
Order By: Relevance
“…An complementary hypothesis is also the direct consumption of Trichodesmium and Katagnymene species by mesozooplankton. Trichodesmium has been considered as a food source for zooplankton species, particularly harpacticoid copepods (O'Neil and Roman, 1994;O'Neil, 1998;Koski and Lombard, 2022). In contrast to our results and with previous studies by Carlotti et al (2018) and Caffin et al (2018); Turner (2014) have shown that high cyanobacteria biomass does not necessarily lead to an increase in zooplankton biomass, as Trichodesmium can be toxic or inedible.…”
Section: Potential Consumption Of Zooplankton On Diazotrophscontrasting
confidence: 90%
See 1 more Smart Citation
“…An complementary hypothesis is also the direct consumption of Trichodesmium and Katagnymene species by mesozooplankton. Trichodesmium has been considered as a food source for zooplankton species, particularly harpacticoid copepods (O'Neil and Roman, 1994;O'Neil, 1998;Koski and Lombard, 2022). In contrast to our results and with previous studies by Carlotti et al (2018) and Caffin et al (2018); Turner (2014) have shown that high cyanobacteria biomass does not necessarily lead to an increase in zooplankton biomass, as Trichodesmium can be toxic or inedible.…”
Section: Potential Consumption Of Zooplankton On Diazotrophscontrasting
confidence: 90%
“…These results can suggest that gelatinous organisms, primarily filter-feeding organisms, likely feed on pico-or nano-cyanobacteria such as the abundant UCYN-A and -B species highlighted by Lory et al (qPCR data from the cruise; see section 4.1, in prep.). Gelatinous organisms also contribute to marine snow, providing a food source for detritivorous organisms that can also consume the large Trichodesmium species (Koski and Lombard, 2022). These filter feeders and detritus feeders are, in turn, likely consumed by carnivorous meso-zooplankton, which exhibit relatively high abundances in our study (Figure 6: gelatinous carnivores, chaetognatha, copepoda, and other larger species).…”
Section: To the Meso-zooplankton Communitymentioning
confidence: 73%
“…Previous studies based on 15 N isotopic measurements on zooplankton reported that the DDN contribution to zooplankton biomass was estimated at ~25% in the Southern Baltic Sea (Wannicke et al, 2013), 30-40% in the tropical Atlantic (Montoya et al, 2002;Loick-Wilde et al, 2016), and 67-75% in the WTSP (Carlotti et al, 2018). Other studies based on direct observations, grazing experiments, or nifH detection in full-gut copepods, report that several copepod species graze on diverse diazotrophs such as Trichodesmium (O'Neil et al, 1996;O'Neil, 1999;Koski and Lombard, 2022), UCYN from groups A, B and C (Scavotto et al, 2015;Hunt et al, 2016;Conroy et al, 2017), Richelia (Hunt et al, 2016;Conroy et al, 2017), and Aphanizomenon (Wannicke et al, 2013;Koski and Lombard, 2022). Finally, 15 Nlabelling experiments revealed that diazotrophs can be a direct source of N supporting the metabolism of zooplankton (Loick-Wilde et al, 2012;Wannicke et al, 2013;Adam et al, 2016;Hunt et al, 2016;Caffin et al, 2018a).…”
Section: Composition Of the Sinking Fluxes In The Wtspmentioning
confidence: 97%
“…This suggests that these organisms may have ingested diazotrophs between 0 and 200 m, consequently decreasing their export flux at 170 m. Trichodesmium spp. has traditionally been considered as a food source for only few zooplankton species, mainly harpacticoid copepods (O'Neil and Roman, 1994) due to its toxicity (O'Neil, 1998), but recent studies suggest that they are grazed by other zooplankton species (Hunt et al, 2016;Koski and Lombard, 2022), although Trichodesmium spp. produces sulfuric compounds repulsive to grazers in Fe deficiency conditions (Bucciarelli et al, 2013).…”
Section: Evaluation Of the Potential Direct Export Of Diazotrophsmentioning
confidence: 99%
“…to be a preferred food choice for M. norvegica (Uye et al, 2002), and they seem to prefer aggregates made up of diatoms (Koski and Lombard, 2022), which may explain the dominance of M. norvegica in the inner fjord.…”
Section: Seasonal and Geographic Abundance Of Microsetella Norvegicamentioning
confidence: 97%